HUBUNGAN PERILAKU MASYARAKAT TERHADAP PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA MASA PANDEMI COVID-19 DI PUSKESMAS RUMBAI - Natassa, Jihan; Wardani, Sri; Sari, Wulan; Syafitri, Fiona (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2023)
Behavior is a very important thing to note in dental and oral health. The behavior that people do depends on the knowledge they have. Dental and oral health is very important because if the teeth and gums are damaged and not cared for it can cause pain, interference with mastication and can interfere with other health. Good oral hygiene can be realized through good and correct knowledge and behavior in maintaining dental and oral health. The purpose of this study was to determine the relationship between behavior and oral health care during the Covid-19 Pandemic at the Rumbai Health Center in 2021. This type of research is a quantitative study with the help of a questionnaire and the design used is a Cross Sectional Design with Accidental Sampling Techniques. The population is 1034 patients and the research sample is 91 patients. The time of the research will be carried out in October - December 2021. The independent variables in this study are knowledge, attitudes, age, education, employment, economic status, government policies while the dependent variable is dental and oral health maintenance. The results of the study showed that there was no relationship between knowledge, attitudes, age, education, employment, economic status and government policies on dental and oral health maintenance. It is hoped that it can add motivational variables and use different designs or methods. Keywords: Behavior, Dental and Oral Health